1977
DOI: 10.1001/archpedi.1977.02120230050009
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hepatic Tumors and Peliosis Hepatis in Fanconi's Anemia Treated With Androgens

Abstract: \s=b\We report the case of a 13-year-old boy who was known to have Fanconi's anemia for five years. For treatment of this condition he was given androgens and corticosteroids. Two months before his death, severe varicella developed complicated by pneumonia, jaundice, and prolonged fever; all of which resolved during a five-week hospitalization. Three weeks later he died of Clostridium septicum sepsis caused by necrotizing enterocolitis. At autopsy he was found to have multiple hepatocellular neoplasms. A strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
19
0
4
Order By: Relevance
“…The macroscopic and microscopic features of HCC are similar in children and adults, but it is becoming clear that differences in histology, presentation, and prognosis require different strategies of management and evaluation 25, 31. The FML carcinoma variant33 occurs in patients mostly age > 10 years (median age in young adults, 20 years33, 47, 48) but has been reported in childhood as early as age 5 years 1, 72, 73. In a recent North American survey, only 1 of the 10 FML tumors reported occurred in children age < 10 years 48.…”
Section: Discussionmentioning
confidence: 99%
“…The macroscopic and microscopic features of HCC are similar in children and adults, but it is becoming clear that differences in histology, presentation, and prognosis require different strategies of management and evaluation 25, 31. The FML carcinoma variant33 occurs in patients mostly age > 10 years (median age in young adults, 20 years33, 47, 48) but has been reported in childhood as early as age 5 years 1, 72, 73. In a recent North American survey, only 1 of the 10 FML tumors reported occurred in children age < 10 years 48.…”
Section: Discussionmentioning
confidence: 99%
“…The reported regression of hepatocellular carcinoma following discontinuance of anabolic steroids has caused some authors to question whether these lesions are truly malignant.30.33,50.51, 71,86 87 Anthony has suggested that hepatocellular carcinoma, regardless of how well-differentiated, is relentlessly progressive and malignant. He added that spontaneous regression is exceedingly rare once malignant neoplasms become manifest, and knew of no case of proven cancer that had regressed following withdrawal of a known or putative causative agent.4 Shapiro and associates87 have suggested that new terminology is needed to describe hepatocellular carcinomas associated with the use of anabolic steroid therapy, since, although they resemble carcinoma histologically, their clinical behavior is sometimes benign.…”
Section: Discussionmentioning
confidence: 99%
“…As drogas injetáveis, como a testosterona cipionato e as preparações em enantato, parecem não afetar a função hepática. No entanto, são reportados casos de adenoma hepático com o uso dessas substâncias (19) . Urhausen et al estudaram a reversibilidade dos efeitos do uso dos esteroides anabolizantes em inúmeras variáveis, entre elas, algumas enzimas associadas à função hepática.…”
Section: Discussionunclassified